(untitled) (International Journal of Engineering and Computer Science, 2015)
Mobile Adhoc Network (MANET) is a special type of wireless network. It is characterized by dynamic topology (infrastructure less), multi-hop communication, limited resources (bandwidth, CPU, battery, etc.) and limited security. In this paper, we focus on the situation that occurs when specialized, sensitive data are sent to the Internet from MANET nodes. These special data types are especially susceptible to security risks such as information leak and data falsification. Therefore, it is necessary for such special data to be forwarded by a secure/trusted gateway which is under control of a trusted network administrator. However, there can be multiple gateways deployed in a MANET, where the cost ineffectiveness makes it difficult for a network administrator to simultaneously manage every gateway. An optimum mechanism is used to select an appropriate gateway out of the multiple gateways based on multiple node metrics: remaining energy and gateway load for interconnected Mobile Ad hoc Network (MANET) with infrastructure network. To choose an optimum gateway node, we use the Multiple Criteria Decision Making (MCDM) method called Simple Additive Weighting (SAW) for the optimum gateway node. SAW method calculates the weights of gateway node by considering these two metrics. Node with the highest weight will be selected as a gateway. Because of the risk of forwarding special data through an unmaintained gateway, we propose a routing protocol, which allows a source node to have all data forwarded to the Internet through a trusted gateway. To achieve the desirable performance, we have implemented routing protocol called Dynamic MANET On demand (DYMO), which works in consideration of application data. Through simulations, we evaluate our protocol in comparison with the conventional DYMO protocol. We conclude through the simulation results that our protocol get better performance in terms of packet delivery ratio and transmission delay